Le royaume de Méroé - Claude Rilly (Afriques)
The Napatan-Meroitic civilisation flourished in the Middle Nile valley from the 8th century BC to the 4th century AD. It inherited from the former Egyptian colonisation cultural patterns that are obvious in religious and ideological fields as much as in institutions or artefacts. One could even speak of a “Pharaonic civilization” with two sides, Egypt and Ancient Sudan. Little is known from the history of the kingdom of Meroe, first because Meroitic texts are in small number and poorly understood and secondly because archaeological excavations are fairly recent and scattered. External sources such as Egyptian, Greek and Roman evidences are scanty and moderately reliable. However recent progress in the archaeology and philology of Ancient Sudan is currently improving the knowledge of this civilisation.